Estratégias de leitura e desenvolvimento da competência leitora: proposta de sequência didática com base no gênero fábula - Silva, Márcia Rosana da (2017)
This dissertation is situated in the line of research Reading, Writing and Teaching of Portuguese Language and its theme is the teaching of reading through strategies which aim to develop the reading competence of students in the 9th grade, secondary school. The low level of proficiency displayed by students in Portuguese Language classes and, more specifically, in text reading classes, demonstrated that they are unable to attribute meaning to what they read; this makes it an activity of low significance, unfit for preparing them for the future exercise of full citizenship. In light of this observation, we have raised a few questions: how was reading taught in Brazilian schools throughout the 20th century? How should reading be taught at schools currently? Which were the models and paradigms that guided the conception of reading through time? What resources must students possess to become proficient readers? How must the teacher perform in order to develop students into proficient readers? These questions have guided our research, leading to the following objectives: to focalize reading and its teaching-learning process, measuring and pinpointing their importance in the social and educational context; and to contribute to the development of the reading competence of students in the 9th grade of secondary school, by the means of acquiring different reading strategies. Our theoretical framework is based on the main socio-interactional research lines which currently guide the teaching of reading in Brazil, with references to authors whose contributions are extremely relevant in this field, such as Smith (1999), Koch & Elias (2006), Solé (2007) and Kleiman (2004, 2013, 2016). For the application of the strategies selected, we propose a didactic sequence for the reading of the fable genre, elaborated upon the model of Dolz, Noverraz and Schnewly (2004), which is a methodology that we consider to be adequate for students’ active learning of reading strategies. The answers to the questions that were raised initially permit us to affirm that the objectives of the research were reached